Ekstraksi Gigi Posterior dengan Kondisi Periodontitis Kronis Sebagai Persiapan Pembuatan Gigi Tiruan Lengkap pada Pasien Diabetes Mellitus - Azda Nurma Himammi; Bambang Tri Hartono (Jurnal Kesehatan Gigi, 2021)
ABSTRACT Periodontal disease is a disease that attacks the tissue that surrounds and supports the teeth consisting of the gingiva, periodontal ligament, cementum and alveolar bone. In patients who have a history of systemic diseases such as diabetes, the patient's oral health can also be affected, one of which is the appearance of periodontal disease. Periodontal disease is related to diabetes mellitus where diabetes mellitus with uncontrolled glucose levels is a risk factor that aggravates periodontal diseases such as gingivitis and periodontitis. Extraction is the act of taking teeth and tooth roots from the socket involving bone tissue and soft tissue in the oral cavity. Tooth extraction or extraction is a treatment procedure that is quite often performed by. There are various factors that influence tooth extraction, including sociodemography. Extraction is more common in patients with low levels of education than in societies with higher levels of education. This condition probably occurs because of the level of individual knowledge. Diabetes mellitus is a chronic chronic disease that has a prevalence that continues to increase every year, this disease is caused by metabolic disorders so that the body cannot control the levels of sugar in the blood. The immune response is impaired in diabetic patients.